Dual Oxidase 1, 2 Gene Expression in Women With Polycystic Ovary Syndrome (PCOS) - Ardeshir Hesampour; Mina Jafarabadi; Shima Rajabi; Elahe Rezayof; Akram Ghahghaei Nezamabadi (Journal of Family and Reproductive Health, 2023)
Objective: Dual oxidases (DUOX1, DUOX2) belong to the NADPH oxidase (NOX) family, which produce H2O2 necessary for thyroid hormone biosynthesis. This study aims to evaluate gene expression for DUOX1, DUOX2 in PCOS patients and its relation with thyroid hormone and magnesium levels. Materials and methods: Totally 88 cases were studied including 24 people with PCOS and hypothyroidism, 44 people with PCOS and normal thyroid function, and 20 hypothyroid patients without PCOS. In comparison 40 healthy controls in the age group of 16-35 years matched for age group and BMI were evaluated. Using Vegaro syringe 5 cc of blood was sampled from all 128 people and after RNA extraction and cDNA synthesis using Real-Time PCR technique, the expression level of DUOX1 and DUOX2 genes was investigated. Results: The results of hormonal tests showed that there is a significant difference between the level of T4, T3, and TSH hormones in hypothyroid patients with or without PCOS in comparison to the control group. Regarding the level of Mg, the results showed that there is a significant difference between the levels of Mg in PCOS group with or without hypothyroidism in comparison to the control group. Gene expression results showed that the relative changes of DUOX1 gene expression in different groups compared to the control group were significantly reduced P<0.05. In the polycystic group with hypothyroidism, the gene expression level showed a decrease compared to the normo-thyroid polycystic group and the hypothyroid non-PCO group, which was statistically significant P<0.05. Conclusion: According to the results of the present study and the previous studies that have been published in the field of Duox1, it can be assumed that the reduction of Duox1 expression can interfere with the oxidative stress system. Further studies with other molecular techniques may help to understand the exact action mechanism of these genes.